2014
DOI: 10.1186/1471-2458-14-847
|View full text |Cite
|
Sign up to set email alerts
|

Self medicated antibiotics in Bangladesh: a cross-sectional health survey conducted in the Rajshahi City

Abstract: BackgroundAntibiotic self medication is highly prevalent in the developing countries due to easy availability and poor regulatory controls for selling these drugs. The purpose of this study was to evaluate the prevalence of self-medication with antibiotics for the treatment of various diseases by the peoples of Rajshahi city in Bangladesh.MethodsA cross-sectional survey was conducted to the patient’s (n = 1300) at eight locations of Rajshahi city in Bangladesh from March to April, 2014. The locations were sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
140
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(163 citation statements)
references
References 27 publications
15
140
4
4
Order By: Relevance
“…They showed that ampicillin, penicillin, tetracycline, sulfonamides chloramphenicol and oxytetracycline were the most commonly used antibiotics in Bangladesh. In the rural area of Bangladesh, antibiotics are consumed more frequently than any other single class of drug, and 28% of the pe p e's expe diture t ph rm cies f r drugs is antibiotics (Biswas et al, 2014b). This is comparable with estimates in other areas where infectious diseases are prevalent (Biswas et al, 2014b).…”
Section: Introductionsupporting
confidence: 72%
“…They showed that ampicillin, penicillin, tetracycline, sulfonamides chloramphenicol and oxytetracycline were the most commonly used antibiotics in Bangladesh. In the rural area of Bangladesh, antibiotics are consumed more frequently than any other single class of drug, and 28% of the pe p e's expe diture t ph rm cies f r drugs is antibiotics (Biswas et al, 2014b). This is comparable with estimates in other areas where infectious diseases are prevalent (Biswas et al, 2014b).…”
Section: Introductionsupporting
confidence: 72%
“…15,24,26 Bangladesh has become a major field of antibiotic misuse and abuse. [26][27][28][29][30] Very sadly, this prevalent malpractice of abusing antibiotics in Bangladesh contributes to add complexity to the danger which may prove to be possibly the greatest threat humans have ever faced. There is much scarcity of medical literature in Bangladesh, on the antibiotic sensitivity pattern and prevalent microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalent aberrations in the practice of using antibiotics in Bangladesh include self-medication, prescription by quacks and non-physicians, non-registered "village doctors", irrational prescription, etc. [2,6,7]. The resultant rises in resistant strains of several bacteria are also seen [4,[8][9][10] and probably much is yet unseen and unnoticed.…”
Section: Introductionmentioning
confidence: 88%